Biologic drugs induced vitiligo: case reports and review of literature - Shao, Xinyi; Chen, Tingqiao; Pan, Xingyu; Chen, Shuang; Chen, Yangmei; Chen, Jin (Frontiers in immunology, 2024)
Biological drugs are extensively used to treat various inflammatory diseases, including psoriasis, atopic dermatitis (AD), and rheumatoid arthritis. While generally effective and safe, these therapies have been increasingly associated with secondary development of vitiligo, especially with anti-TNF α and anti-IL17 drugs. Dupilumab, an IL-4 receptor alpha antagonist used in moderate to severe AD, rarely induces vitiligo. This study reports two cases of new-onset vitiligo following dupilumab treatment for AD. The first case involves an 80-year-old male who developed vitiligo patches appeared on the chest, back, and lower limbs after 2 months of dupilumab therapy. Despite discontinuation of dupilumab, the vitiligo did not regress. The second case describes a 14-year-old female who experienced depigmentation on her forehead one month into dupilumab treatment, with partial improvement of vitiligo lesions over time despite continued therapy. This phenomenon may be due to dupilumab blocking type 2 inflammation, disrupting normal skin homeostasis, and exacerbating type 1 inflammation. These cases, supplemented with a literature review, highlight the potential for biologic drug-induced vitiligo and underscore the need for awareness of such adverse events in clinical practice. The mechanisms underlying this phenomenon likely involve disruption of the Th1/Th2/Th17 cytokine balance, suggesting that targeted therapies may inadvertently exacerbate type 1 inflammation, leading to vitiligo. With the rising use of biologics, clinicians should carefully consider the risk of vitiligo when prescribing these treatments.